Ergonomics and performance of using prismatic loupes in simulated surgical tasks among surgeons – a randomized controlled, cross-over trial - Fan, Xuelong; Yang, Liyun; Young, Nathalie; Kaner, Ilayda; Kjellman, Magnus; Forsman, Mikael (Frontiers in Public Health, 2024)
Introduction: Recently developed prismatic loupes may mitigate the high physical workload and risk of neck disorders associated with traditional surgical loupes among surgeons. However, research in this area, particularly among surgeons, is sparse. This study examined the impact of prismatic loupes on surgeons’ physical workload, musculoskeletal discomfort, and performance during simulated surgical tasks. Materials and methods: Nineteen out of twenty recruited surgeons performed three tasks ( fixed-order) with their own loupes (randomized), low-tilt (LT) and high-tilt (HT) prismatic loupes, in a randomized order. The primary outcomes were the median inclination angles and velocities of the head, trunk, and upper arms and the median muscle activity of the cervical erector spinae (CES), upper trapezius (UT), and lumbar erector spinae (LES) for each pair of loupes. The secondary outcomes were performance (completion time and errors), perceived body-part discomfort, and subjective evaluation of the three pairs of loupes. Results: Using prismatic loupes, either LT or HT, compared with the surgeons’ own loupes yielded lower head inclinations (all p<0.001), lower neck muscle activity (all p<0.05), and lower neck discomfort in indirect comparisons (p<0.01) with no significant difference in surgical errors (p=0.628). However, HT loupes yielded a longer task completion time in two tasks (p<0.001). Most preferred LT (N=12) for its comfort and visual functions. Discussion: The results indicate that prismatic loupes can reduce physical workload in the neck in simulated surgical tasks with no significant difference in surgical errors. Future studies are needed to investigate the long-term effects of prismatic loupes among surgeons.